Corrections to propagators of Quantum Electrodynamics - Fabiano, Nicola (Vojnotehnički glasnik / Military Technical Courier, 2021)
Introduction/purpose: The problem of quantum corrections to propagators in Quantum Electrodynamics (QED) is discussed.Methods: The Dyson–Schwinger equation is employed for correctingpropagators in QED.Results: The observable quantities in QED are finite.Conclusions: QED divergencies can be avoided by redefining physicalquantities in a suitable manner
Keywords: Quantum Electrodynamics; Quantum Field Theory; Renormalization Group